Teaching-Learning Styles & Aids Student’s Preferences among first Year Undergraduate Medical Students in the College of Medicine, University of Missan, Iraq (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objectives: to collect feedback from first year medical students on their perceptions and preferences ofdifferent teaching, learning, and aids methods that are currently used in medical chemistry teaching course.The aim of our study was to compare the more acceptable teaching & aids methods among the first stagemedical students, Missan Medical College. So that best teaching aid and method can be adopted to improvetheir academic performanceMaterials and Methods: a well-structured electronic questionnaire based study was carried out onundergraduate medical students at department of clinical biochemistry, medical college, Missan University,Missan province, Iraq in second semester of academic year 2020-2021. 197 students participated out of 204total, giving 97% response rate, the questionnaire was properly explained. The students were asked to gradeteaching, learning, and aids methods that were used to teach Medical Chemistry module. The responses wasanalysed according to the Likert scale to detect their preferences and favourites toward the statements in thequestionnaire.Results: In our study many items with high satisfaction and least preferences grades was noticed forcombination of teaching, learning, and aids methods. The majority (76%) of the students like the subjectof medical chemistry. Exams preparation techniques, practical exercise lectures, various teaching aidsand other methods have been found excellent and very good methods by the majority of the students. Foreffective teaching of medical chemistry, students opinions and preferences were suggesting a clear mandatein different issues such as usefulness of more preparations techniques for main exams, using more than oneteaching aids (white board + power point presentation) in the lecture. By understanding students perceptions,teaching learning precesses in medical chemistry can be improved 1.